SOSIALISASI DAN EDUKASI TRANSISI KARIR ATLET PELAJAR MENUJU ATLET MAHASISWA MELALUI PENDEKATAN VISUALISASI KREATIF - Kurniati Rahayuni (Dharmas Journal of Sport, 2023)
The purpose of the service is to provide socialization and education regarding the career transitions of student pencak silat athletes who are projected to become student athletes in the Malang Regency area. Career transition is a process of adjustment experienced by athletes when changing careers, including from student athlete to student athlete. Failure to adjust to career transitions can lead to crises, decreased sports and academic performance. This service activity seeks to provide information and knowledge so that student athletes are ready to face career transitions to university students. Service activities are carried out using the lecture method and career creative visualization, in which athletes visualize the integration process between the past, current career and future career. The implications of dedication and research potential in the field of career transition are also discussed in the article.